2006
DOI: 10.1073/pnas.0609411103
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer demonstrates that muscle is not a primary target for non-cell-autonomous toxicity in familial amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal, progressive paralysis arising from the premature death of motor neurons. An inherited form is caused by a dominant mutation in the ubiquitously expressed superoxide dismutase (SOD1). SOD1 mutant expression within motor neurons is a determinant of onset and early disease, and mutant accumulation within microglia accelerates disease progression. Muscle also is a likely primary source for toxicity, because retraction of motor axons from synaptic connections to muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 54 publications
2
108
3
1
Order By: Relevance
“…It has been reported that muscle degeneration can cause denervation and some degenerative changes in motor neurons, including axon terminal degeneration and microgliosis in the spinal cord (71)(72)(73). However, most studies also demonstrate that muscle degeneration is not a primary driver for motor neuron death to the degree observed in ALS (71,72,74,75). Although one study suggested that mutant SOD1 expressed in muscles could drive motor neuron loss (73), the evidence was equivocal and inconsistent with the conclusions of other studies.…”
Section: Mice Expressing Amir-tdp43 Develop Neurodegeneration In Layer Vcontrasting
confidence: 44%
“…It has been reported that muscle degeneration can cause denervation and some degenerative changes in motor neurons, including axon terminal degeneration and microgliosis in the spinal cord (71)(72)(73). However, most studies also demonstrate that muscle degeneration is not a primary driver for motor neuron death to the degree observed in ALS (71,72,74,75). Although one study suggested that mutant SOD1 expressed in muscles could drive motor neuron loss (73), the evidence was equivocal and inconsistent with the conclusions of other studies.…”
Section: Mice Expressing Amir-tdp43 Develop Neurodegeneration In Layer Vcontrasting
confidence: 44%
“…Interestingly, the muscular ARE activation occurs most robustly in type I fibers, possibly because these fibers are more resistant to neuromuscular pathology. A recent study by Miller et al shows that specific knockdown of mutant SOD1 in the muscle alone has no effect on ALS pathology, whereas knockdown in the muscle and MNs together is sufficient to delay disease, suggesting that mutant SOD in the muscle is not a causative factor in ALS onset and progression [(Miller et al 2006)]. Taking these observations into consideration when evaluating our Nrf2-ARE activation in muscle leads us to hypothesize that early distal stress and muscle activation of the Nrf2-ARE pathway are independent of mutant SOD expression in muscle.…”
Section: Discussionmentioning
confidence: 99%
“…As to the identity of the cell types beyond motor neurons that contribute to disease onset, mutant synthesis within muscle has previously been shown not to affect either onset or progression (25). Mutant synthesis within microglia (8,9) or astrocytes (10) strongly accelerates disease progression, but expression in neither cell type seems to affect onset.…”
Section: Discussionmentioning
confidence: 99%